“The Sad Princess” by V. Vasnetsov: Religious Connotations - Vasina, Ekaterina V. (Actual Problems of Theory and History of Art, 2018)
The article examines The Sad Princess, a painting that belongs to the painted cycle entitled Poem of the Seven Fairy Tales which has been the least studied part of artist’s heritage. The article aims at identifying the literary and pictorial religious sources used by Victor Vasnetsov, as well as at semiotic analysis of them in relationship with the didactic nature of the picture. In addition, it offers an attempt to reconstruct the history of the creation of the painting, on which the artist was working for 30 years until his death in 1926, on the basis of his graphic sketches (most of them published here for the first time). As a result, the following religious subjects previously ignored were recognized in the depictions of the walls of the king’s palace in Vasnetsov’s painting: Woman of the Apocalypse, Barlaam and Josaphat, Anika the Warrior. The religious scenes show Vasnetsov’s profound knowledge of biblical texts, patristic, and spiritual literature. The article analyses both textual and visual sources, such as Russian icons, religious ‘lubok’ prints, and miniatures.Victor Vasnetsov formed ‘the second level’ of the semantic content of his pictures with the help of religious subjects. Through it, he expressed the ideas of greed and the inevitable punishment closely connected with the moral message of the tale. It also reflected the apocalyptic feelings developing rapidly at the turn of the 19th-20th centuries. Thus, the discovered religious connotations provide an opportunity to study the canvas and the cycle of Poem of Seven Fairy Tales in terms of their religious and philosophical content.
Keywords: Russian art; late 19th century; early 20th century; Viktor Vasnetsov; The Sad Princess; Poem of the Seven Fairy Tales; religious connotations; heritage